Novel gastroretentive sustained-release tablet of tacrolimus based on self-microemulsifying mixture： in vitro evaluation and in vivo bioavailability test - Wang, Yan-ping; Gan, Yong; Zhang, Xin-xin (Acta pharmacologica Sinica, 2011)
Aim： To develop a novel gastroretentive drug delivery system based on a self-microemulsifying （SME） lipid mixture for improving the oral absorption of the immunosuppressant tacrolimus. Methods： Liquid SME mixture, composed of Cremophor RH40 and monocaprylin glycerate, was blended with polyethylene oxide, chitosan, polyvinylpyrrolidone and mannitol, and then transformed into tablets via granulation, with ethanol as the wetting agent. The tablets were characterized in respect of swelling, bioadhesive and SME properties. In vitro dissolution was conducted using an HCI buffer at pH 1.2. Oral bioavailability of the tablets was examined in fasted beagle dogs. Results： The tablet could expand to 13.5 mm in diameter and 15 mm in thickness duringthe initial 20 min of contact with the HCl buffer at pH 1.2. The bioadhesive strength was as high as 0.98＋0.06 N/cm^2. The SME gastroretentive sustained-release tablets preserved the SME capability of the liquid SME formations under transmission electron microscope. The drug-release curve was fit to the zero-order release model, which was helpful in reducing fluctuations in blood concentration. Compared with the commercially available capsules of tacrolimus, the relative bioavailability of the SME gastroretentive sustained-release tablets was 553.4%±353.8%. Conclusion： SME gastroretentive sustained-release tablets can enhance the oral bioavailability of tacrolimus with poor solubility and a narrow absorption window.